2023
DOI: 10.2460/javma.22.06.0234
|View full text |Cite
|
Sign up to set email alerts
|

Psychological implications of humane endings on the veterinary profession

Abstract: The veterinary profession has a unique responsibility to animals during the final stages of their lives. The veterinarian’s obligations extend to humane endings, involving all species of animals in a range of circumstances including, but not limited to, euthanasia of individually owned animals, euthanasia of animals for research purposes, depopulation of animals during emergencies, and slaughter of animals raised for food. The veterinary profession continues to improve animal welfare through advances in end-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Studies from the 2001 foot-and-mouth disease outbreak in the United Kingdom found that those involved in animal depopulation had negative emotional impacts that included distress, bereavement, and fear ( Mort et al, 2005 ). Surveys of veterinarians involved in swine depopulation efforts associated with the COVID-19 pandemic showed high levels of burnout and emotional trauma ( Baysinger and Kogan, 2022 ; Bussolari et al, 2022 ; Kollias et al, 2023 ). While depopulation is always likely to cause some level of emotional stress on personnel, physical methods of euthanasia have been shown to be associated with higher rates of burnout, compassion fatigue, and poor professional quality of life as compared to nonphysical methods ( LaFollette et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the 2001 foot-and-mouth disease outbreak in the United Kingdom found that those involved in animal depopulation had negative emotional impacts that included distress, bereavement, and fear ( Mort et al, 2005 ). Surveys of veterinarians involved in swine depopulation efforts associated with the COVID-19 pandemic showed high levels of burnout and emotional trauma ( Baysinger and Kogan, 2022 ; Bussolari et al, 2022 ; Kollias et al, 2023 ). While depopulation is always likely to cause some level of emotional stress on personnel, physical methods of euthanasia have been shown to be associated with higher rates of burnout, compassion fatigue, and poor professional quality of life as compared to nonphysical methods ( LaFollette et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A particular stress of working with animals professionally is the requirement to deal with their deaths, often being in charge or participating in euthanasia, slaughter, or depopulation. The impact on the mental health of veterinary teams is a major focus of the American Veterinary Medical Association, which is building sources of support for those involved in the “Humane Endings” of animals in all contexts ( 1 ).…”
Section: Impact On the Animal Care Teammentioning
confidence: 99%
“…In recent years, the issue of burnout and mental health among animal care and health professionals (ACHPs) has received increasing attention in the fields of veterinary science and humananimal interaction (1)(2)(3)(4)(5)(6)(7). ACHPs is a broad term referring to employees or volunteers who look after animals, with roles including, but not limited to, veterinarians, veterinary nurses, animal attendants, wildlife carers, foster carers, zookeepers, and administrative workers (3).…”
Section: Introductionmentioning
confidence: 99%